Lichen diversity as indicators for monitoring ecosystem health in Rawa Danau Nature Reserve, Banten, Indonesia - RIDA OKTORIDA KHASTINI; INDAH JUWITA SARI; YOLA HERYSCA; SITI SULASANAH (Society for Indonesian Biodiversity, 2019)
Abstract. Khastini RO, Sari IJ, Herysca Y, Sulasanah S. 2018. Lichen diversity as indicators for monitoring ecosystem health in Rawa Danau Nature Reserve, Banten, Indonesia. Biodiversitas 19: 489-496. Study on environmental changes is very important in present circumstances throughout the world. Lichen biodiversity may provide an excellent measure in bio-monitoring on the ecosystem health of nature reserve areas such as Rawa Danau in Banten Province, Indonesia. At present, this area is highly disturbed due to ecological factors and human activities such as land use for agricultural land and residential area. The objective of this research is to provide the information needed for assessing ecosystem health which will be revealed by the diversity of lichens in the study area. The study was conducted using transect-based plot in three landscapes: residential area, primary forest and secondary forest, while exploration technique was carried out in freshwater swamp area. The cover for lichen species in the substrates and the number of species present were recorded. Shannon-Wiener diversity index was also calculated. A total of 86 specimens were collected from these four areas which resulted in the occurrence of 25 species of lichens belonging to 20 genera and 14 families. Shannon-Winner’s diversity index are ranging from 1.7197 at residential area to 2.6678 at swamp area. The variation in species composition is likely associated with the abiotic and biotic factors of each landscape with the differences in lichen diversity across landscapes suggest an altered environmental condition of in Rawa Danau. The results of this study can be used as baseline information of ecosystem health of Rawa Danau Nature Reserve in the face of future environmental changes.